Sulfonylureas or biguanides is associated with a lower risk of rheumatoid arthritis in patients with diabetes: A nationwide cohort study - Su, Yu-Jih; Huang, Jing-Yang; Chu, Cong-Qiu; Wei, James Cheng-Chung (Frontiers in Medicine, 2022)
Objective Diabetes mellitus (DM) is associated with immune dysregulation, while sulfonylureas or biguanides have been linked to anti-inflammatory mechanisms. In this study, we aimed to examine the occurrence rate of rheumatoid arthritis (RA) among DM patients and its incidence rate between different treatments. Methods This cohort study used the Taiwan National Health Insurance Research Database between 1997 and 2013 to evaluate the primary outcomes of the preventive role of sulfonylureas or biguanides in the development of RA. We used the Chi-square test for categorical variables and Cox proportional hazard regression and log-rank test to explore the time for development of RA in DM patients. Logistic regression was adopted to estimate the odds ratio of RA in different dosages of medication exposure. Results Our cohort study included 94,141 DM cases. The risk of RA development of non-sulfonylureas/biguanides users among the DM group in each analysis was set as the reference, and the adjusted hazard ratio of RA in DM patients who were using sulfonylureas or biguanides was 0.73 (95% confidence interval 0.60–0.90). Within 1 year before the index date, compared with no-biguanides users, patients with more than 180 days of prescription of biguanides had a significantly lower RA risk. Similarly, the significantly lower risk of RA was still observed in DM patients who had more than 365 days of prescription of sulfonylurea within 2 or 3 years before the index date of first RA visit (all p < 0.05). Conclusion Our data suggest that sulfonylureas or biguanides are associated with a lower rate of RA development in patients with DM; the effect of biguanides appeared more rapid than that of sulfonylureas, but the sulfonylureas might have a longer effect on lowering RA development incidence.